Outbound FDI control: A new economic security tool for the European Union? - Sophie Meunier; Sarah Bauerle Danzman (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
The European Union is considering implementing regulations and possible prohibitions on outbound FDI in some high-technology sectors. These deliberations are part of a substantial re-evaluation of the security implications of economic interdependence. This Perspective contextualizes the EU's recent interest in outbound controls and explores potential challenges of such actions.
Keywords: 330